2017
DOI: 10.1111/1753-6405.12616
|View full text |Cite
|
Sign up to set email alerts
|

Food and beverage price discounts to improve health in remote Aboriginal communities: mixed method evaluation of a natural experiment

Abstract: Objective: Retrospectively evaluate food price discounts in remote Aboriginal community stores. Methods:Four price discount strategies of 10% were designed in 2010, aiming to influence grocery, fruit, vegetables and diet soft-drink sales. This natural experiment across a group of stores was evaluated using an explanatory, sequential mixed method design through analysis of store point-of-sale, document, observation and interview data. The outcome was measured by change in: 1) percentage of grocery sales to tota… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
77
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(78 citation statements)
references
References 28 publications
1
77
0
Order By: Relevance
“…The majority of studies were conducted in the United States (n = 56) or Canada (n = 13) . Studies encompassed food service (n = 44), grocery (n = 56), and mixed (n = 7) retail settings including cafeterias (n = 24), full service restaurants (n = 18), corner stores and/or grocery stores (n = 19), supermarkets (n = 16), vending machines (n = 13), quick‐service restaurants (n = 13), and cafés (n = 5) . Approximately half of thes...…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The majority of studies were conducted in the United States (n = 56) or Canada (n = 13) . Studies encompassed food service (n = 44), grocery (n = 56), and mixed (n = 7) retail settings including cafeterias (n = 24), full service restaurants (n = 18), corner stores and/or grocery stores (n = 19), supermarkets (n = 16), vending machines (n = 13), quick‐service restaurants (n = 13), and cafés (n = 5) . Approximately half of thes...…”
Section: Resultsmentioning
confidence: 99%
“…Six initiatives were retailer‐led, 29 were the result of partnerships, and 41 were researcher‐led, with the remainder government‐, industry‐, or health organization‐led. More than half of the included studies (n = 66) identified one or more business outcomes in the primary aim of the study.…”
Section: Resultsmentioning
confidence: 99%
“…This energy–cost differential helps explain the persistently poor dietary patterns reported in this population 43 . Despite this, research suggests that community dietary patterns can be improved through improved food supply and stock management in community stores 45,46 . Consequently, the focus of Aboriginal and Torres Strait Islander nutrition‐based initiatives has broadened to include improving food quality and access to healthy food in remote communities, 45,46 rather than a sole focus on nutrition education.…”
Section: Discussionmentioning
confidence: 99%
“…5,6 However, sustainable, at-scale uptake of these policies has been limited in part because of the current paucity of research identifying factors which drive successful implementation. Within the existing literature, there has been some exploration of the experiences of retailers involved in healthy food interventions, [7][8][9][10][11][12][13][14][15][16][17] and some research drawing on researchers' own experiences of implementation. 7,8,16,18 However, there is little literature capturing the comprehensive experiences of implementation, across the range of stakeholders involved in designing and implementing the policy.…”
Section: Introductionmentioning
confidence: 99%